ECONOMIC EFFICIENCY OF COFFEE IN THE SOUTH OF MINAS GERAIS: ONE APPLICATION OF PRODUCTION FRONTIER - Freire, Adriano Higino; Reis, Ricardo Pereira; Veiga, Ruben Delly; Fontes, Renato Elias (Coffee Science - ISSN 1984-3909, 2011)
Through this study, we sought to evaluate the economic efficiency of the allocation of productive resources of coffee inthe south of Minas Gerais. The cities surveyed are among the largest producers in the south of this state: Alfenas, Guaxupé, SãoSebastião do Paraíso, Varginha and Tres Pontas, totaling 46 coffee plantations. This study is based on the principles of the theory ofproduction and cost, using the stochastic production frontier model to measure and estimate the production function. The technicalcoefficients refer to the agricultural years 2006/2007, 2007/2008 and 2008/2009, which were adjusted for the 2008/2009 harvest. Onaverage, farmers have an economic efficiency of 70.3%. Coffee producers were considered cost efficient when the measure ofeconomic efficiency (EE) was equal to or greater than 90.0%. The percentage of farmers who have achieved this minimum score ofefficiency stands at 28.2%. The results indicate inefficient use of productive resources in most cases, both technically and economically